Prevalência de hipertensão arterial sistêmica na atenção primária à saúde de regiões urbanas de Santa Maria - RS - Neves, Gabriela Leal (2018)
This study aims to evaluate the prevalence of people with or without a medical diagnosis of hypertension, arterial pressure changed, met in primary health care of the Midwest regions, East Centre and East the urban Santa Maria/RS. It is an analytical cross-sectional study, carried out by means of a field research, quantitative approach. Sampling was done randomly, systematics and proportional to the size of the population registered by administrative region divided by sex and age group. Inclusion criteria were to be user, of both sexes, of primary care in the urban area of the municipality; have to 20 to 79 years of age. The data were collected by means of a semi-structured interview. Were measured blood pressure, weight, height, waist, abdominal and hip circumferences, in addition to the rates of total cholesterol and fractions, blood glucose and triglycerides. Cardiovascular risk was stratified with Framingham risk scale. The analyses were carried out in the Statistical Package for Social Sciences software version 17.0. Ethical issues respected the resolution 466/12 of the National Health Council. 154 people participated in the research (78 men and 76 women) with an average age of 44 years. The majority of the population declared themselves ethnic white, single, Catholic, uneducated or incomplete elementary education, entered the job market, residing between three and four people, with per capita income less than one minimum wage, home ownership, masonry, treated water and sewage collection pipe network. 57,1% stated not ingest alcohol, 85,1% not being active smokers, 57,8% no smoking and 52,6% not practicing physical activity. 31,2% of people stated antidepressant treatment and 55,2% are considered stressed. 37,01% of people are overweight, 76,31% of women with central obesity. The inappropriate lifestyle modification is part of the drug treatment of hypertension and blood pressure levels control. Therefore, the change of habits reveals important since 33,77% of people reported high blood pressure, however the levels 51,95% pressure changed at the time of research. This change was observed in 53,33% of people from 30 to 39 years. Blood pressure changes were frequent in men after 30 years and in women after 50 years of age. In addition, family event premature, dyslipidemia, diabetes mellitus family kidney disease and peripheral vascular disease were more risk indicators associated with the low, medium and high risk. 33,77% was stratified at high risk, 30,52% with low and 3,9% intermediary. 16,13% people with low risk have changes in blood glucose and 83,33% with changes in average HDL-c. The risk stratification was effectively revealing the urgent need to adopt effective preventive measures and early tracking of blood pressure. Therefore, this research contributes to the scientific breakthrough allowing the planning of actions in health for a comprehensive and coherent care practice with regard to the needs of the population.